Combination of bioelectrochemical systems and electrochemical capacitors: Principles, analysis and opportunities - Caizán-Juanarena, Leire (Biotechnol Adv, 2020)
Bioelectrochemical systems combine electrodes and reactions driven by microorganisms for many different applications. The conversion of organic material in wastewater into electricity occurs in microbial fuel cells (MFCs). The power densities produced by MFCs are still too low for application. One way of increasing their performance is to combine them with electrochemical capacitors, widely used for charge storage purposes. Capacitive MFCs, i.e. the combination of capacitors and MFCs, allow for energy harvesting and storage and have shown to result in improved power densities, which facilitates the up scaling and application of the technology. This manuscript summarizes the state-of-the-art of combining capacitors with MFCs, starting with the theory and working principle of electrochemical capacitors. We address how different electrochemical measurements can be used to determine (bio)electrochemical capacitance and show how the measurement data can be interpreted. In addition, we present examples of the combination of electrochemical capacitors, both internal and external, that have been used to enhance MFC performance. Finally, we discuss the most promising applications and the main existing challenges for capacitive MFCs.